The EFFECT OF DIVIDEND POLICY AND PROFITABILITY ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MEDIATOR - bahri, erik sagita (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study aims to examine the direct effect and indirect effect between Dividend Policy, Profitability, and CSR on Firm Value. The sample in this study is a consumer non-cyclicals company listed on the Indonesia Stock Exchange from 2019 to 2021 which uses purposive sampling, namely companies that pay dividends. The sample obtained was 152 companies Design/methodology/approach : The analysis technique used is the regression analysis and path analysis Findings: The results of this study indicate that: (1) Dividend Policy not affect Firm Value , CSR and Profitability affect Firm Value, (2) CSR is able to mediate the effect of Dividend Policy on Firm Value, (3) CSR is unable to mediate the effect of Profitability on Firm Value. Future researchers are expected to use all companies listed on the Indonesian stock exchange so that it is easier to get the complete data information needed because it is more widespread not only focusing on one sector. Research limitations/implications: The implication of the results of this study is as a basis for company policy in assessing the performance of the company. Where when the company is consistent in distributing dividends, the company's value will be high, this is also supported by the profitability of the company. In addition, the CSR factor carried out by the company can certainly also increase the value of the company Where when the company is consistent in distributing dividends, the company's value will be high, this is also supported by the profitability of the company. In addition, the CSR factor carried out by the company can certainly also increase the value of the company. The more CSR that is done, the better the company's performance. Originality/value: This research is original Paper type: Research paper